'Imbecile hopes': dispositions of subjectivation in Joseph Conrad's Lord Jim and Nostromo. Issue 8 (3rd August 2022) - Gooch, Joshua
ABSTRACT: This essay considers how Joseph Conrad's novels Lord Jim and Nostromo explore political subjectivation as a disposition-making process capable of unleashing feelings in new and inhuman forms. By examining trust and hope as dispositions which organise discourses, signs, and feelings, the essay brings forward a tension in Conrad's understanding of subjectivation for white imperial agents between an older form of subjectivity based on rights and contracts exemplified by trust and character, and an emergent form of subjectivity based on economic interests and success exemplified by hope.